Evaluation of Transdermal Formulations of Metoclopramide Prepared Using Arachis Oil and Liquid Paraffin as Permeation Enhancers - Sylvester O. Eraga; Matthew I. Arhewoh; Ogochukwu A. Meko (Mazandaran University of Medical Sciences, 2020)
Background: The study aimed to evaluate the effect of arachis oil and liquid paraffin on metoclopramide release from transdermal films. Objectives: Batches of metoclopramide films were prepared with hydroxypropyl methyl cellulose (HPMC), arachis oil or liquid paraffin and Tween 80 as plasticizer. The films were evaluated for their physiochemical properties, in vitro and ex vivo drug release and drug release kinetics. Drug-excipient interactions were investigated using Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared (FTIR) spectroscopy. Methods: The transdermal films had a weight range of 0.22-0.24 g, folding endurance of 300-306, percentage moisture content and uptake of 2%-10% and 19%-110%, respectively and drug content of 98%-104%. There was similar condition in vitro release profile for the films but their ex vivo profiles exhibited variable drug release with the P3 (30% arachis oil) giving the highest drug (almost 100%) release. Results: The release kinetics of metoclopramide followed the first order and Korsemeyer-Peppas models more closely as seen in their correlation coefficients (R2) of 0.9832 and 0.9560, respectively. Drug-excipient compatibility studies showed no interactions between excipients and metoclopramide. Conclusion: The formulated transdermal films showed controlled drug release over a period of 12 h. Arachis oil and liquid paraffin showed similar permeation enhancing ability. These enhanced permeation properties of the films could be helpful in the development of alternative route for metoclopramide administration in the management of emesis with improved patient acceptance.